Proceedings of the 1st International Conference on Inter-Professional Health Collaboration (ICIHC 2018) 2019
DOI: 10.2991/icihc-18.2019.83
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Of Different Toothbrush Type On Plaque Removal In Orthodontic Patients

Abstract: Background: Current treatment of fixed orthodontic currently used by many, not only for orthodontic treatment but also part of a modern lifestyle. Treatment of fixed orthodontic is treatment aimed to fix malocclusion and increase awareness of dental care, mastication function, and esthetic. Aims: This research is to acknowledge the effect of orthodontic toothbrush, soft and flat toothbrush and zigzag from toothbrush to decrease index plaks for the fixed orthodontic user. Methods: Quasi-experimental research de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
2
0
0
1
Order By: Relevance
“…A statistically significant difference was noted in dental plaque accumulation before and after cleaning in both groups. These results are in agreement with Gomes et al ( 2012 ) and Kurnianti and Razi ( 2019 ) findings. This could be explained by the fact that the participants were instructed on how to remove dental plaque using different means.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A statistically significant difference was noted in dental plaque accumulation before and after cleaning in both groups. These results are in agreement with Gomes et al ( 2012 ) and Kurnianti and Razi ( 2019 ) findings. This could be explained by the fact that the participants were instructed on how to remove dental plaque using different means.…”
Section: Discussionsupporting
confidence: 93%
“…This variation could be attributed to the fact that in vitro studies are likely to occur in a more controlled environment.In the current study, no statistically significant difference was found between the DWJ and the O-TH. This result agrees with the one reported bySoni et al (2012), which suggested that both O-TH and DWJ are effective oral hygiene tools.A statistically significant difference was noted in dental plaque accumulation before and after cleaning in both groups.These results are in agreement withGomes et al (2012) andKurnianti and Razi (2019) findings. This could be explained by the fact that the participants were instructed on how to remove dental plaque using different means.…”
supporting
confidence: 93%
“…Hasil penelitian tersebut menunjukkan sikat gigi khusus ortodontik lebih baik dari kedua sikat gigi konvensional dalam penurunan IP dengan menggunakan teknik roll dan modifikasi bass. 22 Pertimbangan dalam pemilihan sikat gigi pada penelitian ini selain memiliki bulu sikat halus, rata tapi juga tapered dengan tujuan agar bulu sikat dapat masuk ke sulkus gusi dan ke sela-sela sekeliling band dan bracket, sehingga dapat membersihkan plak secara optimal. 5,6,8 Hasil penelitian terdahulu menggunakan 2 teknik sikat gigi yaitu teknik roll dan modifikasi bass yang memiliki kelemahan dalam menjangkau pada permukaan tertentu, khususnya plak di daerah interdental, sulkus gusi dan di bawah band dan bracket.…”
Section: Research Articleunclassified